The influence of K2CO3 to rice husk ratio for CO2 adsorption in fixed bed column. (February 2020) - Elizabeth, L; Heriyanto,
Abstract: Carbon dioxide emissions contributed by fossil fuel, have become a severe concern in relation to global warming and health issues. High content of CO2 will caused low content of heat value. This study is to reduce the concentration of CO2 gas by adsorption using K2 CO3 rice husk. The method used is adsorption using a laboratory scale fixed bed column equipment at atmospheric condition and room temperature. The adsorption column was filled with K2 CO3 and rice husk which composition (50: 8; 75: 8; 100: 8; 125: 8) grams, CO2 gas flowed from the bottom of the column which flow rate 9 liter per minutes (LPM). Then the sample was taken at the top of the column every 5 minutes. It showed that the highest adsorption capacity is 7.54 percent CO2 removal/gr adsorbent which amount of K2 CO3 adsorbent 50 gr at 9 LPM CO2 inlet flow rate. It showed that most adsorbents have the most active sites to adsorb CO2 . It also showed that K2 CO3 50 gr have the longest breakthrough time than others amount of K2 CO3 .